Impact of Safety-Net Burden on In-Hospital Mortality and Hospitalization Costs Among Patients with Alcoholic Hepatitis and Alcoholic Cirrhosis. (19th August 2020) - Ladhani, Sanah; Hirode, Grishma; Singal, Ashwani K; Wong, Robert J
Abstract: Aims: Alcoholic hepatitis (AH) and alcoholic cirrhosis disproportionately affect ethnic minority and safety-net populations. We evaluate the impact of a hospital's safety net burden (SNB) on in-hospital mortality and costs among patients with AH and alcoholic cirrhosis. Methods: We performed a cross-sectional analysis of 2012–2016 National Inpatient Sample. SNB was calculated as percentage of hospitalizations with Medicaid or uninsured payer status. Associations between hospital SNB and in-hospital mortality and costs were evaluated with adjusted multivariable logistic regression and linear regression models. Results: Among 21, 898 AH-related hospitalizations, compared to low SNB hospitals (LBH), patients hospitalized in high SNB hospitals (HBH) were younger (44.4 y vs. 47.4 y, P  < 0.001) and more likely to be African American (11.3% vs. 7.7%, P  < 0.001) or Hispanic (15.4% vs. 8.4%, P  < 0.001). AH-related hospitalizations in HBH had a non-significant trend towards higher odds of mortality (OR 1.27, 95% CI 0.98–1.65, P  = 0.07) and higher mean hospitalizations costs. Among 108, 669 alcoholic cirrhosis-related hospitalizations, patients in HBH were younger (53.3 y vs. 55.8 y, P  < 0.001) and more likely to be African American (8.2% vs. 7.3%, P  < 0.001) or Hispanic (24.4% vs. 12.0%, P  < 0.001) compared to LBH. Compared to alcoholic cirrhosis-related hospitalizations in LBH, mortality was higher among medium SNB (OR 1.10, 95% CI 1.03–1.17, P  = 0.007) and HBH (OR 1.07, 95% CI 1.00–1.15, P  = 0.05). Mean hospitalization costs were not different by SNB status. Conclusions: HBH hospitals predominantly serve ethnic minorities and underinsured/uninsured populations. The higher in-hospital mortality associated HBH particularly for alcoholic cirrhosis patients is alarming given its increasing burden in the USA. Abstract : Short Summary: Patients hospitalized with alcoholic cirrhosis or AH at high safety-net burden (SNB) hospitals were more likely to be African American or Hispanic. Hospitalizations among higher SNB hospitals were associated with significantly greater mortality, particularly for patients with alcoholic cirrhosis.